Workshop of Learning Equipment at SMK KAL-1 Surabaya: Workshop Perangkat Pembelajaran di SMK KAL-1 Surabaya - Bagus Dwi Cahyono; Irwanto (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Vocational High School is an educational institution that produces products in the form of Human Resources who have a level of competence that can be accepted and needed in the business and industrial world. The service activity in the form of a K13 learning device workshop at SMK KAL 1 Surabaya is a synthetic activity and application of all lecture material in the field of study, education that has been obtained through the lecture mechanism in the form of institutional management performance and learning management. In this learning tool workshop, 2 forms of data collection techniques are used, namely post-test and assessment in the form of a rating scale using a Likert Scale. The instrument used in this study was a test instrument used to obtain data on the level of teacher knowledge of learning and assessment tools, as well as obtain data on performance results and the feasibility of preparing lesson plans. The implementation of service at SMK KAL-1 Surabaya has a positive impact. Where it can be seen from the results of the teacher's knowledge test before the implementation of the pre-test workshop it was obtained 64.95, and after the post-test workshop it was obtained 92.63. Through an assessment using a rating scale with a Likert scale reference, 5 lesson plans with eligibility criteria are very good or very feasible.